THE EXTRA CLASS ACTIVITY IN IMPROVING STUDENT’S VOCABULARY - Assyifa, Nadya Noor (LINGUAMEDIA Journal, 2023)
A good vocabulary is important in language learning. Students often struggle to expand their vocabulary due to limited learning time. Additional classroom activities, such as supplementary classes, are effective in improving students' vocabulary. This study uses a qualitative approach with document analysis method and also aims to evaluate the impact of supplementary classes on students' vocabulary knowledge and use, identify the types of activities that are effective, as well as the factors that influence the effectiveness of supplementary classes. The results of this study show that supplementary classes can improve students' vocabulary. Interactive and creative activities are effective in promoting vocabulary learning. Factors such as student motivation, learning strategies, and parent and teacher support affect the effectiveness of supplementary classes. Schools and teachers should certainly develop additional learning activities or so-called supplementary classes. With it supports students' vocabulary improvement. In conclusion, supplementary classes are an effective alternative if the right factors are in place.